Loving Mrs. Bontrager - Lough, Loree (Lough, Loree. Little child shall lead them., 2021)
"Between raising three grieving children and running a booming business, recent widower Aaron Bontrager desperately needs help--even if it means a marriage of convenience only. He couldn't be more surprised by his new wife, ebullient Bethel Mast. With an unconventional, joyful sense of purpose, she's starting to turn his house back into a home and bring stability and peace to his children's lives...Bethel never had a fair chance for a home and family of her own...and she soon finds Aaron's formidable exterior hides a sensitivity and caring that she's quietly drawn to"--